Concurrent sprint swimming interval and dryland training: Performance and biomechanical variable changes within a mesocycle - Arsoniadis, G. G.; Chalkiadakis, I.; Toubekis, A. G. (Applied Sciences, 2024)
The aim of this study was to examine the effects of concurrent dryland and sprint swimming interval training (SIT), and of SIT only, on swimmers` performance and biomechanical variables before, during, and following 6 weeks of training. Twenty-four swimmers (age: 16.5 ± 2.9 years) were assigned to three groups of equal performance level and applied concurrent dryland and SIT three times per week, as follows: (i) maximum strength (three sets × four repetitions, load 90% of one-repetition maximum) [1RM]) prior to SIT (group: G-MS); (ii) muscular endurance (2 sets × 20 repetitions, load 55% of 1RM) prior to SIT (group: G-ME); and (iii) SIT only (consisting of 2 series of 4 × 50 m sprints (group: G-CON)). Performance time, stroke rate (SR), stroke length (SL), and stroke index (SI) were measured during 4 × 50 m sprints. For pre- vs. post-performance time, SR, SL, and SI were similar between groups (p > 0.05). SR increased in G-MS and G-ME in week 6 vs. week 1 (p = 0.02), while SL and SI were similar between groups (p > 0.05). Concurrent dryland compared with sprint interval swimming training on the same day may progressively increase SR within a 6-week period, and all types of training improved front crawl efficiency following a mesocycle of training.